Reconciliation(s): transitional justice in postconflict societies - Quinn, Joanna R. (Studies in nationalism and ethnic conflict, 2009)
'Reconciliation(s)' considers the definition of the concept of reconciliation itself, focusing on the definitional dialogue that arises from the attempts to situate reconciliation within a theoretical and analytical framework